2011
DOI: 10.1007/s00426-011-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the allocation of attention in the Stroop task: evidence from eye movement patterns

Abstract: Attention plays a crucial role in the Stroop task, which requires attending to less automatically processed task-relevant attributes of stimuli and the suppression of involuntary processing of task-irrelevant attributes. The experiment assessed the allocation of attention by monitoring eye movements throughout congruent and incongruent trials. Participants viewed two stimulus arrays that differed regarding the amount of items and their numerical value and judged by manual response which of the arrays contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Only very few studies assessed eye movements in the flanker task (Machado and Franz, 2004;Peschke et al, 2013) and in a numerical Stroop task (Olk, 2013). Those studies showed that eye movement patterns reflect the conflict (Peschke et al, 2013) and also allow to assess the allocation of attention as well as the resolution of the conflict (Olk, 2013). However, those studies did not include TMS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only very few studies assessed eye movements in the flanker task (Machado and Franz, 2004;Peschke et al, 2013) and in a numerical Stroop task (Olk, 2013). Those studies showed that eye movement patterns reflect the conflict (Peschke et al, 2013) and also allow to assess the allocation of attention as well as the resolution of the conflict (Olk, 2013). However, those studies did not include TMS.…”
Section: Discussionmentioning
confidence: 97%
“…This may be of particular importance when spatial attention is addressed. In the word-color version word and color occupy the same location but other versions, e.g., a numerical version, provide the opportunity to spatially separate attributes of the stimuli that are critical for the conflict in the incongruent condition (Washburn, 1994;Olk, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Olk (2013) was the first to track eye movements while performing the Stroop test. The objective of the study was to determine how Stroop interference is reflected in the attention allocated by participants, by tracking their eye movements while they performed the task.…”
mentioning
confidence: 99%
“…Participants are asked to name the colour of the words presented as fast as they can [ 22 25 ]. This becomes more difficult to do if the colour is incongruent with the word [ 23 25 ]. It is easier to name the word ‘red’ if it is printed in red than if it is green.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter situation, this conflict slows responding which leads to the ‘Stroop effect’ [ 23 25 ]. The scores on the task reflect how well participants can selectively direct attention to task relevant features while ignoring task-irrelevant features [ 23 25 ]. In our study, participants were asked to read the colour of words (blue, red, green) on a sheet of paper as fast as they can.…”
Section: Methodsmentioning
confidence: 99%